Niveles de acumulación de cadmio y plomo por el tallo de Cortaderia rudiuscula Stapf “cortadera” - Anticona Cosavalente, Thamara Yhajaira (2018)
The present investigation argues one of the most valued techniques in the history of the environment to achieve its recovery, phytoremediation, takes advantage of the ability of certain plants to accumulate, metabolize, volatilize or stabilize contaminants present in the soil. The objective of the study was to determine the accumulation levels of cadmium 4.0, 8.0, 12.0, 16.0, 20.0 ppm and lead 20.0, 40.0, 60.0, 80.0, 100.0 ppm by the stem of Cortaderia rudiuscula Stapf "cortadera", for this the biological material was collected in the district of Agallpampa, Otuzco, La Libertad; in an area free of mining activity. The experimental work was carried out in the laboratory of Environmental Genotoxicity of the Faculty of Biological Sciences, National University of Trujillo, having two systems, lead and cadmium respectively and two control group; Three repetitions were performed for each treatment. After a period of adaptation of the plant, the research was conducted in a white light photoilumination environment for 8 days, for which an experimental design of increasing stimulation was applied, completely randomized, with six treatments and three repetitions for each system. The sampling of the stems was done every 48 hours in a period of 8 working days, the samples were analyzed in the Chemical Engineering Laboratory of the UNT using the instrumental method of atomic absorption spectrophotometry. The results obtained were analyzed through the InfoStat program, where it was obtained that the stem of C. rudiuscula shows accumulative capacity for lead with 0.4780 ppm, which suggests that it could be used in environmental phytoremediation plans; however, for cadmium a value of 0.0462 ppm was obtained.